Investigação da indução de metabólitos em soja [Glycine max (L.) Merr.] frente à herbivoria por Spodoptera frugiperda (J. E. Smith) (lepidoptera: noctuidae) - Costa, Josicleia Oliveira (2025)
Soybean (Glycine max (L.) Merrill) is a crop of great economic and nutritional importance, widely cultivated in Brazil and around the world. However, its cultivation faces significant challenges, with pest attacks being one of the main threats to productivity. Among these pests, the fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), stands out due to its high adaptability and resistance to traditional control methods, such as the use of insecticides. This insect is capable of attacking plants from the early developmental stages to the reproductive phases, compromising both yield and crop quality. The intensive use of insecticides has had negative impacts on the agroecosystem, which drives the search for more sustainable strategies, such as studying the natural resistance of plants and the metabolites involved in this interaction. In this study, the induction of metabolites in young and old soybean leaves at different vegetative stages (VC, V2, and V5) subjected to herbivory by S. frugiperda was investigated. Through untargeted metabolomic analysis, performed by UHPLC-Q-TOF-MS/MS, it was possible to identify and annotate a variety of primary and secondary metabolites, with a focus on fatty acids, phenolic acids, and terpenoids. The results showed that the VC and V2 stages were the most responsive to stress caused by herbivory, exhibiting greater metabolic changes. In contrast, the V5 stage showed less metabolic induction, with compounds exclusively related to primary metabolism. At the same time, the effect of induced resistance in the different vegetative stages on the biological development of S. frugiperda was assessed. For this, the plants were subjected to previous herbivory experiments, and in bioassays, the caterpillars were fed with previously induced leaves. The parameters analyzed included larval, pupal, and adult weights, as well as leaf consumption. The results revealed that the VC and V2 stages had a significant impact on the development of S. frugiperda. At the VC stage, there was a substantial reduction in pupal and adult weights, while at the V2 stage, there was a significant decrease in larval and adult mass. On the other hand, the V5 stage was more susceptible, allowing more favorable caterpillar development, without significant changes in the biological parameters evaluated. These findings reinforce that leaf age and plant development stage directly influence both the magnitude of the metabolic induction response and the development of S. frugiperda, highlighting the importance of considering these variables in the sustainable management of agricultural pests.